2005
DOI: 10.3928/01484834-20050301-06
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study to Investigate the Effect of a Simulation Strategy on the Clinical Decision Making of Midwifery Students

Abstract: The actual effect of the use of simulations on clinical decision making is inconclusive. This pilot study used a posttest design to determine the effect of a simulation strategy on the clinical decision-making process of midwifery students. Thirty-six graduate diploma students volunteered and were randomly assigned to two groups, with the experimental group receiving two simulation sessions (normal labor and physiological jaundice), and the control group receiving the two usual lectures. The main findings were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(30 citation statements)
references
References 12 publications
0
27
0
3
Order By: Relevance
“…[19] also agrees with the aforementioned author that active engagement in an experience promotes critical thinking skills and improves long-term retention of content. [20] also adds that active learning increases motivation and interest in the learning domain. Another research done by [21] considered past examination results and demonstrated that improvement in critical thinking, improved cognitive retention and enhanced clinical decision-making correlated with low examination rates.…”
Section: Teaching Characteristicsmentioning
confidence: 99%
“…[19] also agrees with the aforementioned author that active engagement in an experience promotes critical thinking skills and improves long-term retention of content. [20] also adds that active learning increases motivation and interest in the learning domain. Another research done by [21] considered past examination results and demonstrated that improvement in critical thinking, improved cognitive retention and enhanced clinical decision-making correlated with low examination rates.…”
Section: Teaching Characteristicsmentioning
confidence: 99%
“…Four studies analysed the effect of simulation on critical thinking development (Cioffi et al, 2005;Scholes et al, 2012;Lendahls and Oscarsson, 2017;Amod and Brysiewicz, 2017). Contradictory results were found between the studies, with three reporting an increase in critical thinking following the intervention (Cioffi et al, 2005;Lendahls and Oscarsson, 2017;Amod and Brysiewicz, 2017) and one study finding poor application of critical thinking to the simulation scenarios (Scholes et al, 2012). These results may reflect differences in how students were prepared for the activity, complexities of the simulation, and how critical thinking was measured.…”
Section: Critical Thinking Development and Measurement In Midwiferymentioning
confidence: 99%
“…Alternatively, standardized patients (SPs) could appear in the clinical environment, with providers (the study participant) blinded to the SP’s true identity. SPs could use checklists, 87 tallies, timing intervals, 88 global assessments, and affective responses as outcomes. Performance assessments of physicians by SPs have found high concordance with other measures of performance 89–92 .…”
mentioning
confidence: 99%